Profile of delamanid for the treatment of multidrug-resistant tuberculosis - Szumowski JD; Lynch JB (Dove Medical Press, 2015)
John D Szumowski,1,2 John B Lynch11Division of Allergy and Infectious Diseases, Department of Medicine, University of Washington, Seattle, WA, USA; 2Division of AIDS Medicine, Santa Clara Valley Medical Center, San Jose, CA, USA Abstract: New approaches to the treatment of multidrug-resistant and extensively drug-resistant tuberculosis (TB) are badly needed. Not only is the success rate of current treatment regimens suboptimal but existing regimens require multiple drugs and lengthy courses and may lead to significant toxicities. The treatment landscape is beginning to shift, however, with the recent approvals of the new TB drugs bedaquiline and delamanid. Delamanid, a dihydro-imidazooxazole, has been shown to have excellent activity against Mycobacterium tuberculosis in both in vitro and in murine TB models. It has also recently been reported to improve rates of sputum culture conversion in patients with multidrug-resistant TB when added to an optimized background regimen. Although generally well tolerated, delamanid has been associated with QT prolongation, which may be of particular clinical concern when paired with other TB drugs that may also have this effect, most notably the fluoroquinolones. Ongoing studies will help to clarify delamanid’s role in the treatment of drug-resistant TB. Keywords: delamanid, OPC-67683, Deltyba, tuberculosis